The ectodomains determine ligand function in vivo and selectivity of DLL1 and DLL4 toward NOTCH1 and NOTCH2 in vitro - Lena Tveriakhina; Karin Schuster-Gossler; Sanchez M Jarrett; Marie B Andrawes; Meike Rohrbach; Stephen C Blacklow; Achim Gossler (eLife, 2018)
DLL1 and DLL4 are Notch ligands with high structural similarity but context-dependent functional differences. Here, we analyze their functional divergence using cellular co-culture assays, biochemical studies, and in vivo experiments. DLL1 and DLL4 activate NOTCH1 and NOTCH2 differently in cell-based assays and this discriminating potential lies in the region between the N-terminus and EGF repeat three. Mice expressing chimeric ligands indicate that the ectodomains dictate ligand function during somitogenesis, and that during myogenesis even regions C-terminal to EGF3 are interchangeable. Substitution of NOTCH1-interface residues in the MNNL and DSL domains of DLL1 with the corresponding amino acids of DLL4, however, does not disrupt DLL1 function in vivo. Collectively, our data show that DLL4 preferentially activates NOTCH1 over NOTCH2, whereas DLL1 is equally effective in activating NOTCH1 and NOTCH2, establishing that the ectodomains dictate selective ligand function in vivo, and that features outside the known binding interface contribute to their differences.